1985
DOI: 10.1095/biolreprod33.4.981
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction of a Tissue Collagenase Associated with Ovulation in the Rat1

Abstract: A method has been developed to assay collagenase in ovarian extracts in the presence of tissue inhibitors. Rat ovarian tissue is first extracted with Triton X-100 and then heated to 60 degrees C in 50 mM Tris buffer containing 100 mM CaCl2. This extract contains collagenase activity and putative inhibitor(s). The inhibitory activity is removed by reduction with dithiothreitol and alkylation with iodoacetamide. Collagenase is then activated with aminophenylmercuric acetate and assayed using 3H-acetylated collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Increased collagenolytic activity in the preovulatory follicles of rabbit ovaries was demonstrated (Kawamura et al, 1981). Curry et al (1985) also reported the preovulatory increase of MMP-1 activity in the rat ovary.…”
Section: Discussionmentioning
confidence: 89%
“…Increased collagenolytic activity in the preovulatory follicles of rabbit ovaries was demonstrated (Kawamura et al, 1981). Curry et al (1985) also reported the preovulatory increase of MMP-1 activity in the rat ovary.…”
Section: Discussionmentioning
confidence: 89%
“…Of course other MMPs with overlapping substrate specificities, such as MMP-2, may account for the lack of a more dramatic ovarian phenotype in the MMP-9 null mice. Based on increased collagenase (against collagen I) activity in ovaries of ovulating rats (21,22) and bovine follicles (62), it is highly likely that MMP-13 plays a role in ovulation. However, the temporal pattern of MMP-13 expression in the rodent ovary (24) and its presence in PRKO mice (J.S.R., unpublished data) indicate that it is not a PR-regulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix metalloproteinases (MMPs) have received considerable attention as candidate proteases controlling ovulation (19). Of the 23 known MMPs (20), collagenases (MMP-13 and MMP-8), which degrade collagen type I, gelatinases (MMP-2 and MMP-9), which degrade collagen types IV͞V, and stromelysin-like enzymes (MMP-19) have been shown to be present in the ovary (21)(22)(23)(24)(25). However, their relationship, if any, to each other or to ovulation has remained speculative.…”
mentioning
confidence: 99%
“…Both serine proteases (Danø et al 1985) and matrix metalloproteinases (MMPs) (Birkedal-Hansen et al 1993) and their respective inhibitors have been shown to regulate homeostatically the extent and rate of extracellular matrix (ECM) reorganization associated with tissue remodeling. These enzymes or their inhibitors have been shown to be present in ovaries of the cow ( Juengel et al 1994), hamster (Ichikawa et al 1983), human (Curry et al 1990, Duncan et al 1996a, monkey (Duncan et al 1996b), mouse (Waterhouse et al 1993, Inderdeo et al 1996, pig (Smith et al 1994b), rabbit (Espey & Coons 1976), rat (Morales et al 1983, Reich et al 1985, Curry et al 1985, Roche & Ryan 1986, Hirsch et al 1993, Butler & Woessner 1994, Okada et al 1994, Nothnick et al 1995, Balbin et al 1996, and sheep (Murdoch & McCormick 1992, Smith et al 1994a, Russell et al 1995, McIntush et al 1996. The expression of the metalloproteinases and their inhibitors have been primarily studied by biochemical techniques.…”
Section: Introductionmentioning
confidence: 99%